2013
DOI: 10.1179/1743281213y.0000000146
|View full text |Cite
|
Sign up to set email alerts
|

Study on mechanism of mould powder entrapment in funnel type mould of flexible thin slab casting machine

Abstract: A physical model was established to study the mechanism of mould powder entrapment in the funnel type mould of a flexible thin slab casting machine, and the effects of operational parameters on the powder entrapment were investigated. The results show that there are three mechanisms of mould powder entrapment, vis-à -vis entrapment caused by shear stress, entrapment caused by vortex and entrapment caused by shear stress and vortex. Three different modes of the entrapment caused by the shear stress, between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Generally, the mechanisms of slag entrapment can be classified into nine categories [2][3][4]; top surface-level fluctuations, meniscus freezing, vortexing, shear-layer instability, narrow face spout impingement upon the top surface, argon bubble interactions, slag crawling down the submerged entry nozzle (SEN), instability of the top surface standing wave, and top-surface balding. In tandem, Zheng and Zhu [5] found three mechanisms of slag entrapment caused by the shear stress, vortex, and a special mixture of "shear stress and vortex". No matter which mechanism occurs, the slag-source inclusions are likely to be entrapped into the solidified shell [6], downgrading the quality of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the mechanisms of slag entrapment can be classified into nine categories [2][3][4]; top surface-level fluctuations, meniscus freezing, vortexing, shear-layer instability, narrow face spout impingement upon the top surface, argon bubble interactions, slag crawling down the submerged entry nozzle (SEN), instability of the top surface standing wave, and top-surface balding. In tandem, Zheng and Zhu [5] found three mechanisms of slag entrapment caused by the shear stress, vortex, and a special mixture of "shear stress and vortex". No matter which mechanism occurs, the slag-source inclusions are likely to be entrapped into the solidified shell [6], downgrading the quality of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…Slag can be trapped in molten steel mainly due to vortex formation, slag shear due to high velocity, and turbulence near the meniscus. 5 Gupta and Lahiri 6 investigated the flow and vortex near SEN and observed that slag entrapment occurs because of swirl flow in the upper part of the mold. Li et al 7 studied that slag trapping in molten steel occurs when the impacting force exceeds the surface tension force.…”
mentioning
confidence: 99%